Cassava Brown Streak Disease Response and Association With Agronomic Traits in Elite Nigerian Cassava Cultivars - Ano, Chukwuka Ugochukwu; Ochwo-Ssemakula, Mildred; Ibanda, Angele; Ozimati, Alfred; Gibson, Paul; Onyeka, Joseph; Njoku, Damian; Egesi, Chiedozie; S. Kawuki, Robert (Frontiers in Plant Science, 2021)
Cassava mosaic geminiviruses (CMG) and Cassava brown streak virus (CBSV) cause the highest yield losses in Africa's cassava production. Cassava brown streak disease (CBSD) in particular has been and continues to be a significant constraint to optimal cassava production in eastern and southern Africa. While CBSD has not been reported in West Africa, its recent rapid spread and damage to cassava productivity in Eastern and Southern Africa is alarming. The study involved pre-breeding activities to minimize CBSD impact in the event that it invades Nigeria, the world's largest cassava producer. The study availed information on whether there are useful CBSD resistance alleles present in the elite Nigerian cassava accessions. A total of 1980 full-sib cassava seedlings from 106 families were assessed in the field at seedling stage and a subset of 569 clones were selected and assessed at clonal stage in Namulonge, central Uganda; a known hotspot for CBSD screening. Results indicated that foliar, root incidences and severities varied significantly (p≤0.01, p≤0.001) except for CBSD incidence at six months. Lowest and highest plot-based heritability estimates for CBSD were registered for CBSDrs (0.71) and CBSD6i (0.5). Positive and highly significant correlations were noted between CBSDri and CBSDrs (r = 0.90***), CBSD6i and CBSD6s (r = 0.89***), CBSD3i and CBSD3s (r = 0.89***). Significant positive correlations were also noted between CBSD3s and CBSD6i (r = 0.77***), CBSD3s and CBSD6s (r = 0.78***), CBSD3s and CBSDri (r = 0.40***), CBSD3s and CBSDrs (r = 0.35***). On the other hand, FreshRW negatively correlated with CBSD6i, CBSD6s, CBSDri and CBSDrs respectively (r = -0.52***, r = -0.45***, r = -0.21*** and r = -0.22***). Similarly, CBSD3s correlated negatively with CMD3i, CMD3s, CMD6i and CMD6s respectively (r = -0.25***, r = -0.25***, r = -0.20***, and r = -0.21***). 15 CBSD tolerant cassava genotypes were selected using a non-weighted rank summation selection index. Conclusively, results revealed that the elite Nigerian accessions exhibited significant susceptibility to CBSD within the first two years of evaluation. It is expected that this information will aid future breeding decisions for the improvement of CBSD resistance among Nigerian cassava varieties.